The figure of the funeral officiant and the history of Cremation in the Modern Era - Alfano, Linda; Malcotti, Ivano; Fontana, Paolo; Ciliberti, Rosagemma (Medicina Historica, 2023)
This paper aims at examining the factors that have favoured the spread of cremation in Italy, such as secularisation, the evolution of religious traditions, and people’s desire to enjoy greater freedom of choice in funeral practices. In this context the authors have analysed the figure of the funeral officiant, exploring his relationship with the community and the way in which his presence, and actions, contribute to the creation, during the funeral ceremony, of a greater sense of belonging and support. By analysing the history of cremation in Italy, and the role of the funeral officiant, the authors aim to offer an in-depth perspective on the transformation of funerary practices in Italy, from a cultural and ethical point of view.